Pruritus in patients with amyopathic dermatomyositis - Poddighe, Dimitri (Allergy Asthma Clin Immunol, 2019)
Amyopathic dermatomyositis has been associated with the exposure to several drugs: the article by Jeimy et al. described the onset of this uncommon disease in a patient treated with omalizumab. Paradoxically, this patient complained of an intense pruritus and this finding has been reported by several authors observing patients with amyopathic dermatomyositis.